Comprehensive analysis of histophysiology, transcriptomics and metabolomics in goslings exposed to gossypol acetate: unraveling hepatotoxic mechanisms - Yu, Jun; Yang, Haiming; Wang, Jian; Huang, Zixin; Chen, Shi; Zhao, Hongchang; Wang, Jun; Wang, Zhiyue (Frontiers in Veterinary Science, 2025)
Cottonseed meal is a promising alternative to soybean meal in poultry feed, but concerns over free gossypol limit its use. Although the general toxicity of free gossypol is well-known, its specific effects on the liver—the primary site where it accumulates—are less thoroughly studied, particularly at the molecular level. This study investigated the hepatotoxic effects of gossypol acetate (GA) on goslings through a comprehensive analysis combining morphology, transcriptomics, and metabolomics. Forty-eight 7-day-old male goslings with similar body weight (BW) were randomly assigned to two groups: a control group, receiving a saline solution (0.9%, 2.5 mL/kg BW), and a GA-treated group, administered GA at 50 mg/kg BW orally for 14 days. Histological analysis revealed signs of liver damage, including granular degeneration, hepatocyte enlargement, necrosis, and mitochondrial injury. Transcriptomic analysis identified 1,137 differentially expressed genes, with 702 upregulated and 435 downregulated. Key affected pathways included carbon metabolism, glycolysis/gluconeogenesis, pyruvate metabolism, propanoate metabolism, TCA cycle, fatty acid degradation, primary bile acid biosynthesis, tryptophan metabolism, cysteine and methionine metabolism, focal adhesion, and the PPAR signaling pathway. Metabolomic analysis revealed 109 differential metabolites, 82 upregulated and 27 downregulated, implicating disruptions in linoleic acid metabolism, arachidonic acid metabolism, cAMP signaling, and serotonergic synapse pathways. Overall, GA-induced hepatotoxicity involves impaired energy production, disrupted lipid metabolism, and abnormal liver focal adhesion, leading to liver cell dysfunction. These findings highlight the vulnerability of mitochondria and critical metabolic pathways, providing insights into the molecular mechanisms of GA toxicity and guiding future studies on mitigating GA-induced liver damage in goslings.